Processing of PLA/sisal fiber biocomposites using direct- and extrusion-injection molding. Issue 5 (4th April 2017) - Chaitanya, Saurabh; Singh, Inderdeep
ABSTRACT: The processing strategy adopted to develop biocomposites plays a significant role in determining their characteristics. The present experimental investigation explores the feasibility of using direct-injection molding (D-IM) process for processing of sisal fiber (3 mm and 8 mm) reinforced poly-lactic acid biocomposites with a fiber weight fraction of 30%. For a comparative analysis, mechanical and morphological behavior of biocomposites developed using D-IM process is compared with biocomposites developed using extrusion-injection molding (E-IM) process. The mechanical behavior in terms of tensile, flexural and impact properties is compared and discussed in relation to extracted fiber morphology and fiber orientation as well as dispersion within the developed biocomposites. Morphological investigation of extracted fibers revealed severe fiber attrition and fiber length variation during E-IM process as compared with D-IM process. However, short sisal fiber (3 mm) reinforced biocomposites developed using both the processes exhibit uniform fiber dispersion and orientation, resulting in comparable mechanical properties. The tensile and flexural strength of D-IM-SF biocomposites increased remarkably by 34.7% and 15.9%, respectively, as compared with D-IM-LF biocomposites. Similarly, the tensile and flexural modulus of D-IM-SF biocomposites increased significantly by 92.5% and 56.7%, respectively, as compared with D-IM-LF biocomposites. However, D-IM process incorporating long fibers exhibit better impact properties.